Influence of physiological conditions on hemodynamics of internal carotid artery aneurysms - Lei Zhou; Shanjie Dong; Amir Alahdadi Kheiri (Scientific Reports)
Abstract This study investigates the influence of body physiology on the rupture risk of cerebral saccular aneurysms. Comprehensive hemodynamic analyses were conducted using computational fluid dynamics to assess the potential for aneurysm rupture under three physiological conditions: rest, normal activity, and exercise. Contours of wall shear stress, oscillatory shear index, and pressure were analyzed and compared to identify regions at high risk of rupture. Additionally, statistical analysis was performed to evaluate the rupture risk of aneurysms. Blood flow dynamics during the peak systolic phase were also examined under these conditions. Our findings indicate that the dome area, where blood pressure is highest and the incoming blood flow first contacts the aneurysm sac, is the critical region with a heightened risk of rupture.